Tangent Cultural Interaction and Postcolonial Hybrid Societal Edifice in Hanief Kureshi’s “My Son The Fanatic” - Anwar, Ansa; Irshad, Aasma; Batool, Maria; Bin Zubair, Hassan (Civil Officium: Journal of Empirical Studies on Social Science, 2021)
This study set out to identify the types of hybridity that arise from postcolonial cultural interaction with colonial formation. The depictions of Parvez and Ali from Hanif Kureshi's short story My Son the Fanatic are hybrids, according to researchers. The Homi K. Bhabha concept of hybridity was used in this study, which followed a post-colonialist strategy. Bhabha's viewpoint (1994), it is the result of a tangential interaction in distinct cultures. In this instance, hybridity is understood to be the result of the dominance of colonial power dynamics which involves not only the merging of cultures but also cultural objects that are situated in social as well as historical space as a result of post-colonialism. Due to its significance in analyzing descriptive text in predetermined literary works, the qualitative descriptive approach was employed in this research. According to the research's findings, there are two different ways that hybridity is represented in this research. First, because of the content creation that was created, mimicry has a character that is ambiguous and contradictory in the context of cultural fidelity. Parvez, an individual in the narrative, serves as a metaphor for mimicry. Second, Ali, his son, represented ambivalence in the story. Ali resisted the construction because he understood how colonialism discriminated against his culture, but he was confused about what identity he should adopt. The short story "My Son the Fanatic" by Hanif Kureishi depicts cultural hybridity through the characters Parvez and Ali, who represent mimicry and ambivalence resulting from the dynamics of colonial and postcolonial power.